2019
DOI: 10.1101/gr.243212.118
|View full text |Cite
|
Sign up to set email alerts
|

OMA standalone: orthology inference among public and custom genomes and transcriptomes

Abstract: The correction has been made in the revised article online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 95 publications
0
130
0
Order By: Relevance
“…To examine gene families that may have undergone expansions in association with functional divergence and specialization, we identified groups of orthologous genes that have increased and decreased in size in the two genomes, relative to one another. We identified these species-specific gene-family expansions using the Orthologous MAtrix (OMA) standalone package [74]. OMA predicted 8817 OMA groups (strict 1:1 orthologs) and 8578 Hierarchical Ortholog Groups (HOGs, Additional file 8).…”
Section: Gene Family Expansionsmentioning
confidence: 99%
“…To examine gene families that may have undergone expansions in association with functional divergence and specialization, we identified groups of orthologous genes that have increased and decreased in size in the two genomes, relative to one another. We identified these species-specific gene-family expansions using the Orthologous MAtrix (OMA) standalone package [74]. OMA predicted 8817 OMA groups (strict 1:1 orthologs) and 8578 Hierarchical Ortholog Groups (HOGs, Additional file 8).…”
Section: Gene Family Expansionsmentioning
confidence: 99%
“…(a) We inferred a set of markers by running the OMA standalone algorithm 92 on a set of 149 archaeal genomes chosen to represent known taxonomic diversity. We inferred single protein trees for 97 orthologues that were present in at least 75% of the genomes and manually inspected the resulting trees to identify and remove 15 markers that had undergone gene transfer, resulting in a final set of 82 candidate single-copy orthologs.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that the hypothesized lineage of the cutinase gene emerged after its transference between distantly related plant-degrading microbes through lateral gene transfer events (LGTs) (Belbahri et al, 2008). Genes that evolved from what is considered to be an "ancient" duplication event (i.e., duplication before speciation as in the case of Pzezizomycotina and subsequent speciation events that occurred after a single duplication event) may have diverged to an extent that created new functions (Altenhoff et al, 2019).…”
Section: Orthologue Detection In 200 Fungal Genomes and Implicationmentioning
confidence: 99%